2020
DOI: 10.1002/advs.201903746
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Derived from Human Umbilical Cord Mesenchymal Stem Cells Protect Liver Ischemia/Reperfusion Injury by Reducing CD154 Expression on CD4+ T Cells via CCT2

Abstract: As a cause of postoperative complications and early hepatic failure after liver transplantation, liver ischemia/reperfusion injury (IRI) still has no effective treatment during clinical administration. Although the therapeutic potential of mesenchymal stem cells (MSCs) for liver IRI has been previously shown, the underlying mechanisms are not completely clear. It is accepted that MSC‐derived extracellular vesicles (MSC‐EVs) are newly uncovered messengers for intercellular communication. Herein, it is reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
61
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 64 publications
1
61
0
Order By: Relevance
“…[142] For example, Zheng et al demonstrated the key role of Chaperonin containing TCP1 subunit 2 (CCT2) enriched in extracellular vesicles excreted from umbilical cordderived mesenchymal stem cells in the amelioration of the liver IRI (Figure 9). [143] This CCT2-mediated attenuation of liver IRI might result from the downregulation of CD154 level expressed on CD4 + T cells, one main cause of IRI-related inflammatory environments, via Ca 2+ -calcineurin-nuclear factor of activated T cells 1 (NFAT1) pathway. Anger et al found that mesenchymal stromal cell-derived extracellular vesicles could elevate the levels of Ki67-positive hepatocytes and decrease the expression of inflammation-associated genes in mice bearing with hepatic IRI, suggesting a significant potential to attenuate liver damage and improve organ regeneration after hepatic IRI.…”
Section: Nanoparticulate Drug Delivery Systems Targeting Iri-related Inflammationmentioning
confidence: 99%
See 2 more Smart Citations
“…[142] For example, Zheng et al demonstrated the key role of Chaperonin containing TCP1 subunit 2 (CCT2) enriched in extracellular vesicles excreted from umbilical cordderived mesenchymal stem cells in the amelioration of the liver IRI (Figure 9). [143] This CCT2-mediated attenuation of liver IRI might result from the downregulation of CD154 level expressed on CD4 + T cells, one main cause of IRI-related inflammatory environments, via Ca 2+ -calcineurin-nuclear factor of activated T cells 1 (NFAT1) pathway. Anger et al found that mesenchymal stromal cell-derived extracellular vesicles could elevate the levels of Ki67-positive hepatocytes and decrease the expression of inflammation-associated genes in mice bearing with hepatic IRI, suggesting a significant potential to attenuate liver damage and improve organ regeneration after hepatic IRI.…”
Section: Nanoparticulate Drug Delivery Systems Targeting Iri-related Inflammationmentioning
confidence: 99%
“…Reproduced with permission. [143] Copyright 2020, WILEY-VCH.…”
Section: Nanoparticulate Drug Delivery Systems Targeting Iri-related Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…And a newly published study from the United States put out a novel antifibrotic approach directly targeting signal transducer and activator of transcription 3 (STAT3), which was an important transcription factor associated with liver fibrosis, and this process was accomplished based on the administration of MSCs-derived exosomes embedded with small interference RNAs and antisense oligonucleotides [107]. As for whether MSC-EVs can improve the prognosis of liver transplantation patients, most of the recent studies focused on the process of ischemia-reperfusion injury (IRI) after surgery [108][109][110]. It was reported that the administration of MSC-EVs ameliorated IRI perhaps by enhancing autophagy [108], increasing cell viability and suppressing nuclear factor kappa B activity in hepatocytes [109], or reducing CD154 expression on CD4 + T cells via chaperonin containing TCP1 subunit 2 (CCT2) [110].…”
Section: The Paracrine Of Mscs In Protecting Recipients Of Livermentioning
confidence: 99%
“…As for whether MSC-EVs can improve the prognosis of liver transplantation patients, most of the recent studies focused on the process of ischemia-reperfusion injury (IRI) after surgery [108][109][110]. It was reported that the administration of MSC-EVs ameliorated IRI perhaps by enhancing autophagy [108], increasing cell viability and suppressing nuclear factor kappa B activity in hepatocytes [109], or reducing CD154 expression on CD4 + T cells via chaperonin containing TCP1 subunit 2 (CCT2) [110]. Although the exact mechanism of MSC-EVs to improve the prognosis of liver transplantation has yet to be fully seen, MSC-EVs are worth recognizing as an emerging and very promising therapeutic agent, especially in the regulation of immune rejection.…”
Section: The Paracrine Of Mscs In Protecting Recipients Of Livermentioning
confidence: 99%